Kako preprečiti, da Vrhovno sodišče postane vir neenotne sodne prakse - Betetto, Nina (Podjetje in delo, 2015)
Conflicting decisions in similar cases heard in the same court which, in addition, is the court of last resort in the matter may, in the absence of a mechanism which ensures consistency, breach the principles of predictability and legal certainty and thereby undermine public confidence in the judiciary. The author notices the existence of an inconsistent and non-uniform case law of the Supreme Court of the Republic of Slovenia and discusses the (in)formal mechanisms capable of removing the judicial inconsistency in Slovenian law in similar cases stemming from this court. The notion of a grand chamber in comparative law is also discussed. The author suggests an introduction of such a mechanism to the Supreme Court of the Republic of Slovenia and the corresponding amendment to the Courts Act.
Keywords: sodna praksa; sodne odločbe; vrhovna sodišča